Labio hinchado: una reacción no mediada por la histamina - Telma Elias; Ana Clara Dinis (Sociedade Galega de Medicina Interna, 2021)
Angioedema is a potentially fatal adverse effect, sometimes seen in patients taking ACEI, with an incidence of 0.1-0.7% 1. It manifests as edema of the lips, tongue, face, upper airway and occasionally gastric mucosa. A 54 year-old-woman who resorted to the emergency room with swollen upper lip with 1 day of evolution, with a past medical history of arterial hypertension controlled with an angiotensin-converting enzyme inhibitor (ACE inhibitor). At physical examination only upper lip edema. At first approach we start treatment with IV clemastine and hydrocortisone but with no improvement after 4 hours observation. Thinking about the use of ACE inhibitor we suspected of angioedema induced by ACE inhibitor, we suspend the ACE inhibitor and after 72h the edema vanished. The treatment consists of the mandatory suspension of the drug in question and supportive treatment. However, angioedema induced by ACE inhibitor is described on literature, the incidence is low. We have to keep this side effect in mind because it seems like an allergic reaction/anaphylaxis but doesn´t respond to the same treatment since it's not mediated by histamine. The suspension of ACE inhibitor must be promptly to avoid a fatal outcome.